Moringa and Spirulina: Mini Review on their use against COVID-19. - ASSANHOU, Assogba Gabin (My University, 2021)
The world woke up in 2020 with a new virus called coronavirus 2019 (COVID-19). The virus spread easily from Wuhan, a western province in China to the whole world and caused a pandemic situation. Some preventive measures such as wearing of face masks and the use of alcohol-based sanitizers have been prescribed by the World Health Organization (WHO). All these measures could not effectively handle the virus, and the world started to search for a new solution by using herbal medicines. This mini-review discusses the use of Moringa and spirulina to combat COVID-19.
Keywords: Moringa; Spirulina; covid-19; Herbal medicines